Empowerment of Coastal Communities in the Growth, Management and Development of Tourism Objects in the Digital Era at Bintan District - Nurhasanah; Abdul Jalal (Kusuma Negara Business School, 2020)
This study aims to explain the potential for maritime-based tourism in Bintan Regency, Riau Islands Province and the welfare conditions of the local community as well as to explain management and development strategies in the digital era in maritime-based tourism areas in Bintan Regency, Riau Islands Province with an overview of tourist attractions, accessibility, facilities and communities. improve social welfare. The research method used is descriptive qualitative. The results of the study show that tourist attractions in maritime-based tourism areas in Bintan Regency, Riau Islands Province are quite diverse, accessibility to reach maritime-based tourism areas in Bintan Regency, Riau Islands Province is quite easy, available facilities still need to be repaired and people who live in tourism-based areas maritime in Bintan Regency, Riau Islands Province is very friendly to immigrants, including tourists. Based on this analysis, an urgent strategy was obtained to stimulate growth, management and development of maritime-based tourism areas in Bintan Regency, Riau Islands Province, including the use of budgets for the development of existing potential, the use of technological advances to increase tourism development, increase tourism cooperation with other regions, improving the quality of the apparatus in the tourism sector, providing facilities and infrastructure for tourism activities, increasing tourism promotion efforts for maritime-based tourism areas at the national and international levels and increasing efforts to improve the environment through empowering local communities in the digital era.